On species preservation and non-cooperative exploiters - Lone Grønbæk Kronbak; Marko Lindroos (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2008)
Game-theoretic fisheries models typically consider cases where some players harvest a single common fish stock. It is, however, the case that these types of models do not capture many real world mixed fisheries, where species are biological independent or dependent. The present paper considers cases where several non-cooperative exploiters are involved in mixed fisheries. This paper is targeting biodiversity preservation by setting up a two species model with the aim of ensuring both species survive harvesting of exploiters adapting a noncooperative behaviour. The model starts out as a multi-species model without biological dependency and is then modified to include also biological dependency. We contribute to the literature by analytically finding the limits on the number of players preserving both species including the conditions to be satisfied. For visual purposes we simulate a two species model with different kind of interrelationship.
Keywords: C70; Q22; Q28; 330; biodiversity preservation; non-cooperative game; multi-species; fisheries; bio-economic modelling; Postkeynesianismus; Makroökonomik; Dogmengeschichte